Pengembangan Lembar Kerja Peserta Didik Berbasis Model Kooperatif Tipe Jigsaw pada Pembelajaran Tematik Tema Benda-Benda di Sekitar Kita di Kelas V SD - Dewi Sekar Sari; Hasanah Hasanah (Departement of Mathematics Education, 2024)
This research aims to: 1) Find out how to develop student worksheets based on the jigsaw type cooperative model for thematic learning on the theme of objects around us that are good for fifth grade elementary school students; 2) Knowing the suitability of Student Worksheets based on Jigsaw Type Cooperative Models for thematic learning on the theme of objects around us which are suitable for use by fifth grade elementary school students. This research uses the Thiagarajan development model, namely the 4-D model. This model consists of 4 development stages, namely: Define, Design, Develop and Disseminate. The subjects involved were one material expert, one media expert, one language expert, class V homeroom teacher, and class V students at SDN No. 105375 Sukasari. Experts provide assessments on the suitability of products developed by researchers, while homeroom teachers and students provide responses to products developed by researchers. The results of this research are: 1) produce a product in the form of a Student Worksheet Based on a Jigsaw Type Cooperative Model for Good Thematic Learning on the Theme of Objects Around Us; 2) The product developed is declared suitable for use in class V elementary school, based on the validation results from material experts, namely 92.72% with a very valid category, validation results by media experts, namely 81.81% with a valid category, validation results from language experts, namely 85% with valid category, the results of teacher responses were 85.33% in the very valid category, and the results of student responses were 87.27% in the very valid category.